MicroRNA-505 functions as a tumor suppressor in endometrial cancer by targeting TGF-α - Chen, Shuo (Mol Cancer, 2016)
BACKGROUND: Endometrial carcinoma (EC) is one of the most lethal gynecologic cancers. Patients frequently have regional or distant metastasis at diagnosis. MicroRNAs are small non-coding RNAs that participate in numerous biological processes. Recent studies have demonstrated that miR-505 is associated with several types of cancer; however, the expression and function of miR-505 have not been investigated in EC. METHODS: miR-505 expression in normal endometrial tissue, endometrial carcinomas were quantified by Quantitative reverse transcription PCR. The endometrial carcinoma cell lines HEC-1B and Ishikawa were each transfected with miR-505 or scrambled mimics, after which cell phenotype and expression of relevant molecules were assayed. Dual-luciferase reporter assay and a xenograft mouse model were used to examine miR-505 and its target gene TGF-α. RESULTS: RT-PCR results demonstrated that miR-505 was significantly downregulated in human EC tissues compared to normal endometrial tissues. Besides, miR-505 expression was negatively associated with FIGO stage (stage I-II vs. III-IV), and lymph node metastasis (negative vs. positive). In vitro, overexpression of miR-505 significantly suppressed EC cell proliferation, increased apoptosis and reduced migratory and invasive activity. A miR-505 binding site was identified in the 3′ untranslated region of TGF-α mRNA (TGFA) using miRNA target-detecting software; a dual luciferase reporter assay confirmed that miR-505 directly targets and regulates TGFA. RT-PCR and Western-blotting results indicated that overexpressing miR-505 reduced the expression of TGF-α and the TGF-α-regulated proteins MMP2, MMP9, CDK2, while induced Bax and cleaved-PARP expression in EC cells. In vivo, overexpression of miR-505 reduced the tumorigenicity and inhibited the growth of xenograft tumors in a mouse model of EC. CONCLUSIONS: Taken together, this study demonstrates that miR-505 acts as tumor suppressor in EC by regulating TGF-α. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12943-016-0496-4) contains supplementary material, which is available to authorized users.